2017
DOI: 10.1021/acs.nanolett.7b02222
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Emission from Single Localized Defects in Two-Dimensional Semiconductor to Surface Plasmon Polaritons

Abstract: Coupling of an atom-like emitter to surface plasmons provides a path toward significant optical nonlinearity, which is essential in quantum information processing and quantum networks. A large coupling strength requires nanometer-scale positioning accuracy of the emitter near the surface of the plasmonic structure, which is challenging. We demonstrate the coupling of single localized defects in a tungsten diselenide (WSe) monolayer self-aligned to the surface plasmon mode of a silver nanowire. The silver nanow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…With this demonstration, a directional outcoupling of the quantum light is also necessary for collection. The routing of single photons was successfully demonstrated in plasmonic [102,103] as well as dielectric waveguide [104][105][106]. Statistical analysis of the position of different quantum emitters coupled to plasmonic waveguides showed that they are more likely to form close to the edges of the waveguides [103] with Purcell factor up to 15 ± 3, thus negating the need for pick and place.…”
Section: Integration With Photonic Structuresmentioning
confidence: 99%
“…With this demonstration, a directional outcoupling of the quantum light is also necessary for collection. The routing of single photons was successfully demonstrated in plasmonic [102,103] as well as dielectric waveguide [104][105][106]. Statistical analysis of the position of different quantum emitters coupled to plasmonic waveguides showed that they are more likely to form close to the edges of the waveguides [103] with Purcell factor up to 15 ± 3, thus negating the need for pick and place.…”
Section: Integration With Photonic Structuresmentioning
confidence: 99%
“…An emission enhancement associated with a lifetime reduction was observed, yielding an impressive overall count rate from a single emitter of more than 5×10 6 counts/s at room temperature. The presented technique can be applied to a range of hybrid plasmonic-photonic systems for studying other 2D materials, such as transition metal di-chalcogenides [26][27] and exfoliated hBN monolayers. Further optimization in positioning and improvements in collection efficiency are expected to yield even higher count rates, which will be very attractive for practical devices.…”
Section: ∝ × ×mentioning
confidence: 99%
“…In free space optical measurements, monolayer WSe 2 and other semiconducting TMDs are known to exhibit large light-matter interactions and large third-order nonlinear optical susceptibilities near their exciton resonance 1319 . Recently, there has been significant interest in using monolayer TMDs for plasmonic applications including the demonstration of SPPs coupling to dark excitons in monolayer WSe 2 20,21 , increasing the nonlinear response using localized plasmonic effects 2224 , and enhancement of single quantum emitter emission rates 25,26…”
Section: Introductionmentioning
confidence: 99%